Chemical vapor deposition of guest-host dual metal-organic framework heterosystems for high-performance mixed matrix membranes. (June 2022) - Lin, Yanshan; Su, Pengcheng; Li, Wanbin
Highlights: A new guest-host dual MOF@MOF heterosystem was reported. A solvent-free chemical vapor deposition was used for heterosystem fabrication. The heterosystem has tailored pore geometries and enhanced affinities. The MOF heterosystem has improved compatibility toward polymer. The prepared MMMs show outstanding carbon capture performance. Abstract: Designing metal-organic framework (MOF) architectures and regulating their porous microenvironments are of greatly scientific interests. In this study, we report a kind of guest-host dual MOF@MOF heterosystems with guest MOF cells in other host MOF cavities, and construct them by vapor linker processing. Thanks to the simplified mass transfer process from solvent-free chemical vapor deposition, the pre-impregnated metal precursors in confined MOF pores can be in situ bridged by linkers to form MOF cages with well porosity. These heterosystems exhibit tailored dual pore geometries, enhanced affinities to gas molecules, and combined advantages of different MOFs. We further demonstrate that the MOF@MOF composites have substantially improved compatibility toward polymers and can serve as molecular sieving to adjust membrane transport pathways for achieving outstanding carbon capture performance, with 162% CO2 permeability (14, 366 Barrer, 1 Barrer=10 −10 cm 3 cm cm −2 s −1 cmHg −1 ) and 152% CO2 /N2 selectivity as that of pure polymeric membranes. Our findings provide an alternative perspective for developing heterogeneous and porous materials. Graphical abstract: Image, graphical abstract